UJI POTENSI BOTOl PLASTIK BEKAS AIR MINERAL SEBAGAI MEDIA lEKAT PADA PROSES ANAEROBIK BIOFllTER DAlAM MENURUNKAN KONSENTRASI COD, BOD, DAN TSS L1MBAH CAIR RUMAH TANGGA - Diana Mega Pertiwi; Didik Sugeng P; Siti Surasri (GEMA LINGKUNGAN KESEHATAN, 2013)
Treatment of household wastewater could be difficult because of the high cost andland requirement. An alternative solution to wastewater treatment is the Up Flow AnaerobicBiofilter system. Commonly, Up Flow Anaerobic Biofilter treatment system use bioball asattached growth media. This study did not use bioball media due to the high cost, instead ituse discarded plastic mineral water bottles as an attached growth media. The purpose of thisstudy was to measure the removal efficiency of COD, BOD, and TSS concentrations followingtreatment with anaerobic biofilter system.This study was a quasi-experiment and using a pre-post test design. The studycompared domestic wastewater quality before and after processing with anaerobic biofiltersystem using discarded plastic mineral water bottles as an attached growth media. The depthof the attached growth media in the reactor was 33 cm and the diameter was 30 cm.Acclimatization process was performed for 14 days and operated for 24 days. Samples weretaken six times every four days to examine the COD, BOD, and TSS concentrations.The results obtained of this study are : The average influent COD concentration was254.76 mgjl, effluent COD concentration was 143.57 mgjl and the COD removal efficiency was43.52%. The average influent BOD concentration was 151.01 mgjl, effluent BODconcentration was 109.71 mgjl and the BOD removal effiCiency was 27.21%. The averageinfluent TSS concentration was 43.3 mgjl, effluent TSS concentration was 11.67 mgjl and theTSS removal efflciencv was 72.5%. Based on one sample t-test, the average removalefficiency of COD, BOD, and TSS concentrations were significantly different from thedeslqnated criteria for organic removal efficiency. In other words, it is not efficient (p0,05).It was so because of the operational duration of the anaerobic biofilter was not long enough(24 days) and the initial organic concentration was low.The suggestions for further research are: Controlling influent concentration at stablelevel during operation, controlling the ratio of media and water volume, and calculatingnutrients needed (C, N, P).Keywords: anaerobic biofilter, plastic media, domestic wastewater